2017
DOI: 10.1007/s00404-017-4637-9
|View full text |Cite
|
Sign up to set email alerts
|

The use of barbed sutures for vaginal cuff closure during laparoscopic hysterectomy

Abstract: Vaginal cuff suture performed with barbed suture material is a safe and well-tolerated procedure and reduces operative times. We did not find any meaningful decrease in postoperative vaginal complications including vaginal cuff dehiscence based on the suture material.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…7 Pooled estimates of length of hospital stay [days] and subgroup analysis according to surgery type for the use of VBS versus CS in OB/GYN surgery. Data extracted from references: 8 , 27 , 28 , 31 , 40 45 , 47 51 …”
Section: Resultsmentioning
confidence: 99%
“…7 Pooled estimates of length of hospital stay [days] and subgroup analysis according to surgery type for the use of VBS versus CS in OB/GYN surgery. Data extracted from references: 8 , 27 , 28 , 31 , 40 45 , 47 51 …”
Section: Resultsmentioning
confidence: 99%
“…Some studies suggested that barbed sutures were associated with lower dehiscence rates compared to braided sutures [ 18 ] or braided and monofilament sutures [ 5 ]. Barbed sutures were also associated with shorter operative time [ 31 , 32 ], less post-operative bleeding [ 14 ], shorter hospital stay [ 33 ] and less vaginal cuff granulation at 6 months post-operatively [ 34 ]. The use of unidirectional barbed suture for vaginal cuff closure was found to be safe, with no major complications reported (in a cohort of 121 patients) [ 35 ].…”
Section: Review Of the Literaturementioning
confidence: 99%
“…A large systemic review and meta-analysis found that barbed suture decreased the risk for VCD in TLH and RATLH but a sub-analysis looking only at TLH did not find a difference in VCD rate between barbed suture and traditional absorbable suture [3 ▪▪ ]. Several studies, including a systemic review and meta-analysis of 11 studies, showed that there was no significant difference in VCD rate when comparing absorbable barbed, traditional absorbable, and/or permanent suture [3 ▪▪ ,6 ▪ ,18,21 ▪ ,32–34]. With this mixed information, surgeons should use the appropriate suture they are most comfortable with.…”
Section: Intraoperative Prevention Techniquesmentioning
confidence: 99%
“…With this mixed information, surgeons should use the appropriate suture they are most comfortable with. Although it has not been shown to be superior, barbed suture has the benefit of being self-retaining and knotless and has been shown to decrease vaginal cuff closure time [6 ▪ ,21 ▪ ,31,34]. On the downside, barbed suture is more expensive to use and may not be available in low-resource settings [21 ▪ ,32].…”
Section: Intraoperative Prevention Techniquesmentioning
confidence: 99%